Revitalization of Islamic Education Thru Interactive Learning: Fostering Creativity and Critical Thinking Among Students - Mokhamad Ali Ridlo; Abdul Hanan (Indonesian Journal of Islamic Education and Learning, 2026)
This article aims to examine strategies for revitalizing Islamic education thru the application of interactive learning to foster creativity and critical thinking skills among students. The approach used is qualitative with a library research method, which involves the collection of data from international scientific literature and relevant theoretical books. The findings show that interactive learning in Islamic education enhances student engagement, broadens cognitive horizons, and facilitates the sustainable development of creative and critical character. The implications of this research recommend the integration of active learning strategies such as project-based learning, collaborative learning, and digital technology within the context of the Islamic education curriculum to build 21st-century competencies without neglecting religious values. Interactive learning also serves as a bridge between the tradition of classical Islamic scholarship and modern demands